Universal late pregnancy ultrasound screening to predict adverse outcomes in nulliparous women: a systematic review and cost-effectiveness analysis - Smith, Gordon CS; Moraitis, Alexandros A; Wastlund, David; Thornton, Jim G; Papageorghiou, Aris; Sanders, Julia; Heazell, Alexander EP; Robson, Stephen C; Sovio, Ulla; Brocklehurst, Peter; Wilson, Edward CF (Health technology assessment (Winchester, England), 2021)
Currently, pregnant women are screened using ultrasound to perform gestational aging, typically at around 12 weeks' gestation, and around the middle of pregnancy. Ultrasound scans thereafter are performed for clinical indications only. We sought to assess the case for offering universal late pregnancy ultrasound to all nulliparous women in the UK. The main questions addressed were the diagnostic effectiveness of universal late pregnancy ultrasound to predict adverse outcomes and the cost-effectiveness of either implementing universal ultrasound or conducting further research in this area. We performed diagnostic test accuracy reviews of five ultrasonic measurements in late pregnancy. We conducted cost-effectiveness and value-of-information analyses of screening for fetal presentation, screening for small for gestational age fetuses and screening for large for gestational age fetuses. Finally, we conducted a survey and a focus group to determine the willingness of women to participate in a future randomised controlled trial. We searched MEDLINE, EMBASE and the Cochrane Library from inception to June 2019. The protocol for the review was designed a priori and registered. Eligible studies were identified using keywords, with no restrictions for language or location. The risk of bias in studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) tool. Health economic modelling employed a decision tree analysed via Monte Carlo simulation. Health outcomes were from the fetal perspective and presented as quality-adjusted life-years. Costs were from the perspective of the public sector, defined as NHS England, and the costs of special educational needs. All costs and quality-adjusted life-years were discounted by 3.5% per annum and the reference case time horizon was 20 years. Umbilical artery Doppler flow velocimetry, cerebroplacental ratio, severe oligohydramnios and borderline oligohydramnios were all either non-predictive or weakly predictive of the risk of neonatal morbidity (summary positive likelihood ratios between 1 and 2) and were all weakly predictive of the risk of delivering a small for gestational age infant (summary positive likelihood ratios between 2 and 4). Suspicion of fetal macrosomia is strongly predictive of the risk of delivering a large infant, but it is only weakly, albeit statistically significantly, predictive of the risk of shoulder dystocia. Very few studies blinded the result of the ultrasound scan and most studies were rated as being at a high risk of bias as a result of treatment paradox, ascertainment bias or iatrogenic harm. Health economic analysis indicated that universal ultrasound for fetal presentation only may be both clinically and economically justified on the basis of existing evidence. Universal ultrasound including fetal biometry was of borderline cost-effectiveness and was sensitive to assumptions. Value-of-information analysis indicated that the parameter that had the largest impact on decision uncertainty was the net difference in cost between an induced delivery and expectant management. The primary literature on the diagnostic effectiveness of ultrasound in late pregnancy is weak. Value-of-information analysis may have underestimated the uncertainty in the literature as it was focused on the internal validity of parameters, which is quantified, whereas the greatest uncertainty may be in the external validity to the research question, which is unquantified. Universal screening for presentation at term may be justified on the basis of current knowledge. The current literature does not support universal ultrasonic screening for fetal growth disorders. We describe proof-of-principle randomised controlled trials that could better inform the case for screening using ultrasound in late pregnancy. This study is registered as PROSPERO CRD42017064093. This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 25, No. 15. See the NIHR Journals Library website for further project information.